PECAM-1 Leu125Val (rs688) Polymorphism and Diabetic Nephropathy in Caucasians with Type 2 Diabetes Mellitus - Matej Završnik; Stojan Kariž; Jana Makuc; Maja Šeruga; Ines Cilenšek; Daniel Petrovič (Analytical Cellular Pathology)
Objectives. Platelet endothelial cell adhesion molecule-1 (PECAM-1) plays a key role in the transendothelial migration of circulating leukocytes during inflammation and in the maintenance of vascular endothelial integrity. We hypothesized that genetic variation in PECAM-1 gene could be associated with diabetic nephropathy (DN) and with the level of soluble PECAM-1 in Caucasians with type 2 diabetes mellitus (T2DM). Design and Methods. We analyzed the rs688 single nucleotide polymorphism of PECAM-1 gene C373G (Leu125Val) at exon 3, which encodes the first extracellular Ig-like domain that mediates the homophilic binding of PECAM-1, in 276 T2DM subjects with documented DN (cases) and 375 T2DM subjects without DN (controls), using a polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) strategy. Level of plasma soluble PECAM-1 (sPECAM-1) was measured by ELISA in a subpopulation of 120 diabetics with DN. Results. We found no association between the Leu125Val polymorphism and DN in subjects with T2DM. Likewise, the Leu125Val polymorphism was not associated with serum sPECAM-1 levels in a subpopulation of 120 diabetics with DN. Conclusion. The Leu125Val polymorphism of PECAM-1 and the level of sPECAM-1 are not associated with DN in T2DM subjects of Slovenian origin.